Flexo-elastic and electro-optical studies of some novel liquid crystalline systems - Balachandran, Reshma (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2014)
This thesis presents the experimental investigation of the material properties of liquid crystalline systems composed of (i) bent-core molecules, (ii) bimesogens composed of rod-like molecules and (iii) dimesogens composed of a rod-like and bent-core mesogenic unit. Most of the studies were performed in the nematic phase of these materials.
Keywords: Electronic and Electrical Engineering, Ph.D.; Ph.D. Trinity College Dublin